Correlation between phase angle, body composition, and bioelectrical impedance vector analysis in older adults - De Siqueira Oliveira, Rafaela; Costa Goes, Andréa; Alves Santos, Mylena; De Souza Oliveira, Juliana; Fortes Ferreira, Andrêa Jacqueline; Cruz da Silva Santiago, Emanuelle; Carneiro Roriz, Anna Karla; Cunha de Oliveira, Carolina (Scientia plena, 2025)
Few studies have examined the relation of phase angle (PhA) with body composition and the bioelectrical impedance vector analysis (BIVA) in older adults. The objective of this study was to investigate the correlation between PhA and body composition in community-dwelling older adults and to identify the PhA classification in the position on the RXc graph. A cross-sectional study was conducted with 144 older adults of both sexes. The body composition indicators evaluated included fat-free mass (FFM), fat-free mass percentage (FFM%), skeletal muscle index (SMI), total body water (TBW), body fat (BF), and body fat percentage (BF%). A comparative analysis of PhA and BIVA was also conducted. PhA exhibited an inverse proportional correlation with age, BF%, and TBW, as well as a positive correlation with FFM, FFM%, and SMI (p < 0.05). Individuals with PhA < 5º exhibited higher mean age, FFM, TBW, and SMI (p < 0.05). An evaluation of BIVA revealed that subjects exhibiting a lower PhA were predominantly located in the lower right quadrants for specific tolerance, indicative of a thin body and cachexia. The findings of this study indicated a correlation between PhA and various body composition markers, including FFM, FFM%, BF%, TBW, and SMI. The data presented in the RXc graph demonstrated that older adults with lower PhA were characterized as thin and cachectic. PhA and BIVA have been identified as potential parameters that could facilitate the mapping of nutritional status among older adults. Poucos estudos examinaram a relação do ângulo de fase (AF) com a composição corporal e a análise vetorial de impedância bioelétrica (BIVA) em idosos. O objetivo deste estudo foi investigar a correlação entre o AF e a composição corporal em idosos que vivem na comunidade e identificar a classificação do AF na posição do gráfico RXc. Foi realizado um estudo transversal com 144 idosos de ambos os sexos. Os indicadores de composição corporal avaliados incluíram massa livre de gordura (MLG), porcentagem de massa livre de gordura (%MLG), índice muscular esquelético (IME), água corporal total (ACT), gordura corporal (GC) e porcentagem de gordura corporal (%GC). Também foi realizada uma análise comparativa de AF e BIVA. O AF apresentou uma correlação inversamente proporcional com a idade, %GC e ACT, bem como uma correlação positiva com MLG, %MLG e IME (p<0,05). Os indivíduos com AF <5º apresentaram maior média de idade, MLG, ACT e IME (p<0,05). A avaliação da BIVA revelou que os idosos que apresentavam AF<5º estavam predominantemente localizados nos quadrantes inferiores direitos para tolerância, o que indica magreza e caquexia. Os resultados deste estudo indicaram uma correlação entre o AF e marcadores de composição corporal, incluindo MLG, %MLG, %GC, ACT e IME. Os dados apresentados no gráfico RXc demonstraram que os adultos mais velhos com AF mais baixa foram caracterizados como magros e caquéticos. O AF e BIVA foram identificadas como parâmetros potenciais que poderiam facilitar o mapeamento do estado nutricional entre adultos mais velhos.